(untitled) (London Journal of Medical and Health Research, 2025)
The main goal is to provide a patient who needs help with the change of lifestyle interventions. It also provides a balance of the mind, body, and spirit. Esoteric Science or Energy medicine is the subtle change of a person’s energy and increased spiritual development.